Pemikiran Hukum Islam Kontemporer: Hubungan Fikih, Ushul Fikih, dan Fatwa - Kurniawan, Iwan; Sucipto, Imam (TSAQOFAH, 2026)
Although Islamic law has been the focus of numerous previous studies, research that specifically examines the dialectical relationship among fiqh, usul al-fiqh, and fatwa in contemporary Islamic legal thought remains limited. This study aims to analyze the interconnections among the three main components of the Islamic legal system, namely fiqh as the legal product, usul al-fiqh as the methodology of legal determination, and fatwa as the legal response to contemporary problems faced by the Muslim community. Using a library-based method with analytical-comparative and historical approaches, this study shows that fiqh is the result of scholars’ ijtihad in understanding the scriptural texts of the sharia through the methodologies formulated in usul al-fiqh, whereas fatwa represents the application of fiqh in responding to current issues. The findings indicate that these three elements are bound in a mutually influential dialectical relationship: usul al-fiqh provides the principles and methods for the mujtahid to produce fiqh rulings, fiqh serves as a key reference in the formulation of fatwa, and the evolution of fatwa can, in turn, influence the dynamics of fiqh and even the construction of usul al-fiqh itself. In the contemporary context, a comprehensive understanding of this relationship is crucial for formulating Islamic law that remains responsive to socio-historical developments while firmly rooted in sound sharia principles. This study recommends the development of usul al-fiqh methodologies capable of addressing modern challenges, the enhancement of fiqh ijtihad grounded in in-depth research, and the strengthening of credible and accountable fatwa institutions as strategic efforts to reinforce the relevance of contemporary Islamic law.